Analisis Neraca Air Sesuai Pola Tanam Eksisting Padi Lokal pada Daerah Irigasi Rawa (DIR) Antasan Sutun Kabupaten Banjar - Amal, Nilna; Wulandari, Rizki Ayu (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2024)
The Antasan Sutun Swamp Irrigation Area (DIR), which is located in Sungai Tabuk, South Kalimantan Province, is the source of water for local agricultural land that covers a rice field area of 737.8 Ha. Local farmers have implemented a once-a-year cropping pattern, but there is a need for more water during the dry season. Therefore, this study aims to analyze the amount of availability compared to water demand based on existing cropping patterns. The research method was carried out by analyzing the need and availability of water with a water balance model. Potential evapotranspiration is calculated using the Penman Modification method. The availability of water is calculated using the mock method. The results showed that the maximum water demand discharge was 1.09 m3/sec in March II and a minimum of 0.19 m3/sec in July II. The results of the availability discharge with a maximum mainstay discharge (Q80) of 2.11 m3/sec in January I and a minimum discharge in October II of 0.19 m3/sec. The result showed that all of the moths are water surplus, meaning that the water available in DIR Antasan Sutun can meet the needs of agricultural land with the planting period that the community uses